SMS based value added services with the help of GPS - Rahman, Shahenoor; Shams, Shaba; Islam, Mohammad Sofiqul (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2006.